Strengthening Professional Learning Communities Through Policy and Institutional Support in Diverse Educational Contexts - Rizqi, Putri Umrotur; Syafika, Wanda (Yayasan Sinergi Kawula Muda, 2024)
This narrative review explores the role of Professional Learning Communities (PLCs) in enhancing teacher competencies across various educational settings. The study aims to synthesize empirical evidence on the effectiveness of PLCs in promoting professional development and improving instructional practices. Literature was collected from databases such as Scopus, ERIC, and Google Scholar using keywords including